Hybrid Method for Encoding of Genetic and RC4 Algorithms - Hussein, Marwah Kamil; Salim, Kasim Al; Alhijaj, Asaad (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, the proposed new method used is to generate the encryption key used in the RC4 algorithm by using the genetic algorithm by randomly generating it using the Rand function, and then subjecting it to the randomized conditions approved. If a match is used for coding, otherwise the genetic algorithm will be used to generate the random genetic key, which is along the length of the text to be encrypted.The proposed method used a new structure to hide the encrypted key within the transferred text, in addition to the integrity of the transferred key (integrity) was confirmed by using a simple flux function.